HUBUNGAN DUKUNGAN ORANG TUA DENGAN MOTIVASI BELAJAR ANAK USIA SEKOLAH KELAS V DAN VI DI SD NEGERI 08 LUBUK ALUNG - Yolanda, Mona; Hasanah, Uswatun (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Parental support is support provided by people around a person in the form of emotional, informational and mentoring support which aims to enable individuals to be able to face all the problems that occur in everyday life. People's support also has a big influence on children's success in learning. (Fawzyah et al., 2019). This type of research is a quantitative method that is descriptive correlative in a cross sectional approach. The research was carried out at SD Negeri 08 Lubuk Alung on 22 – 27 July 2024, with a sample size of 50 respondents, with the independent variable being parental support and the dependent variable being motivation to learn. After obtaining data through questionnaires and measuring results, univariate and bivariate data analysis was carried out. The research results showed that more than half of the respondents, namely 34 people (68.0%) had parental support in thepoor category, more than half of the respondents, namely 33 people (66.0%) experienced motivation to learn and it was found using statistical tests (chi-square) that the value was obtained. p= 0.001 (p < 0.05), OR obtained that respondents with low learning motivation are at risk of committing 2,635 times with low learning motivation compared to people with sufficient support. Conclusion of a significant relationship between parental support and learning motivation at SD Negeri 08 Lubuk Alung Padang Pariaman in 2024, the suggestions in this research are expected to provide more attractive facilities so that students' motivation can reappear. So that students will be more active and enthusiasticinlearn.Keywords: Parenteral Support, Learning Motivation.